2014
DOI: 10.11604/pamj.2014.19.148.4195
|View full text |Cite
|
Sign up to set email alerts
|

Le traitement conservateur du cancer du sein: expérience d’une équipe tunisienne

Abstract: En Tunisie, le cancer du sein touche des femmes jeunes avec une taille moyenne au moment du diagnostic à 5 cm. Ces particularités font que la chirurgie radicale reste prédominante. Nous présentons dans ce travail l'expérience de notre équipe en matière de chirurgie conservatrice du cancer du sein. Le but de ce travail est d’évaluer les résultats de ce traitement. Etude rétrospective longitudinale, sur une période de 75 mois. Nous avons inclus toutes les patientes ayant bénéficié d'un traitement conservateur po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The [4]. This increase can be explained by the gradual introduction of conservative surgery into breast cancer management practices, but also by the gradual spread of screening programmes [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The [4]. This increase can be explained by the gradual introduction of conservative surgery into breast cancer management practices, but also by the gradual spread of screening programmes [4].…”
Section: Discussionmentioning
confidence: 99%
“…They may be discovered during targeted screening or in response to clinical signs. In [4]. In Morocco, Mahfoudi et al reported that 95.6% of patients discovered their tumour by the autopalpation method [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differently to other polyphenols, that can generate ROS by undergoing auto-oxidation reactions [157], Morin retains its antioxidant character also at high concentration. Morin is not toxic for animals for doses up to 300 mg/Kg of body weight/day [158], and it is highly effective in protecting cells from oxidant insults generated by oxidants, xenobiotics, excess of metals or radiations. ROS can modulate the function of several transcription factors, influencing the expression of genes involved in the synthesis of proinflammatory cytokines, and can regulate cell survival and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…In these countries, CBE can reduce delay to diagnose breast cancer and it is associated with earlier stage cancer [23]. The average size of breast tumours at the time of their discovery in France was 1.9 cm, whereas it was 5 cm in Tunisia for example [24]. Nevertheless, mammography should be encouraged as biennial mammography reduced in breast cancer deaths compared to annual CBE alone [25].…”
Section: Comparison With Existing Literaturementioning
confidence: 99%